Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

((2 (x - 1))/3) - ((3 (x - 2))/4) = 1​

Sagot :

Answer:

[tex] \frac{2x - 2}{3} - \frac{3x - 6}{4} = 1 \\ \frac{8x - 8 - 9x + 18}{12} = 1 \\ - x + 10 = 12 \\ - x = 12 - 10 \\ x = - 2[/tex]